From The History of Craft Formation in The Ancient World - Kovulov Jurabek (Periodica Journal, 2022)
The article describes in detail the emergence of handicrafts in the ancient world, the origin of this term, the formation of specific types of handicrafts in the countries of the Ancient World and their becoming an integral part of the economy
Keywords: Mesopotamia; Thebes; Sabz; Goddess Ishtar